SYSTEMATIC APPROACH TO NUCLEAR MAINTENANCE TRAINING - Marko Živič (Journal of Energy Technology, 2024)
Qualified personnel directly influence safe and reliable nuclear power plant operations. Operations, surveillance and maintenance personnel are directly responsible for plant safety as well as reliable power generation with their correct professional actions. The training and qualification process in the nuclear power generation industry is separated from the power generation processes. The training and qualification process needs to be supported with proper methodology and suitable training facilities able to ensure transparent and efficient knowledge and skills transfer. The Systematic Approach to Training (SAT) methodology is used as a systematic process that covers the entire training circle from the identification of training needs to training design, training development and training implementation. The final steps of the SAT process are the qualification of training attendees and the documentation of the performed training and qualification process. Performance-based training is performed either on plant equipment mock-ups or on simulator loops whose operation and control is similar to real operating power and safety systems.